Insights Into Oral Manifestations As Diagnostic Indicators Of Viral Infections : A Literature Review - Sovira, Gita Dwi Jiwanda; Achmad Syawqie (Sean Institute, 2024)
Background: Infectious diseases, particularly viral infections, represent a major global health concern, with significant implications for oral health. Despite their clinical relevance, oral manifestations of viral infections are often underdiagnosed due to their complex and varied presentations. Early recognition of these manifestations can aid in timely diagnosis and management, improving overall patient outcomes. Objective: This study aims to systematically review the oral manifestations associated with viral infections to provide a comprehensive reference for healthcare professionals in diagnosing and managing such conditions. Methods: A systematic review was conducted using five databases, including PubMed and Scopus, to identify relevant studies published between 2014 and 2024. Keywords such as